“Motherese” Prosody in Fetal-Directed Speech: An Exploratory Study Using Automatic Social Signal Processing - Parlato-Oliveira, Erika; Saint-Georges, Catherine; Cohen, David; Pellerin, Hugues; Pereira, Isabella Marques; Fouillet, Catherine; Chetouani, Mohamed; Dommergues, Marc; Viaux-Savelon, Sylvie (Frontiers in Psychology, 2021)
Introduction: Motherese, or infant directed speech (IDS), is the specific form of speech used by parents to address their infants. The prosody of IDS has affective properties, expresses caregiver involvement, is a marker of caregiver-infant interaction quality. IDS prosodic characteristics can be detected with automatic analysis. We aimed to explore whether pregnant women ‘speak’ to their unborn baby, whether they use motherese while speaking and whether anxiodepressive or obstetrical status impacts speaking to the fetus. Participants and methods: We conducted an observational study of pregnant women with gestational ages from 26 to 38 weeks. Women were recruited in a university hospital department of obstetrics. Thirty-five women agreed to participate in the study, and 26 audio records were exploitable. We collected obstetrical and sociodemographic data, pregnancy outcomes, anxiety and depressive status using the Covy and Raskin Scales, and life events using the Sensations During Pregnancy and Life Event Questionnaire. Each participant was left alone with an audio recorder with a recommendation to feel free to speak to her fetus as she would have done at home. The recording was stopped after 3 minutes. Audio recordings were analyzed by two methods: psycholinguist experts’ annotation and computational objective automatic analyses. Results: Most mothers (89%) reported speaking to their fetuses. We found a correlation between maternal first perceptions of fetal movements and the start of mother’s speaking to fetus. Motherese prosody was detected with both annotation and automatic analysis with a significant correlation between the two methods. In this exploratory study, motherese use was not associated with maternal anxiodepressive or obstetrical status. However, the more future mothers were depressed, the less they spoke with their fetuses during the recording. Conclusion: Fetal directed speech (FDS) can be detected during pregnancy, and it contains a period of prosody that shares the same characteristics of motherese that can be described as prenatal motherese or emotional fetus-directed speech (e-FDS). This means that pregnant women start using motherese much earlier than expected. FDS seems to be correlated with maternal first perceptions of fetal movements and depression scores. However, more research is needed to confirm these exploratory results.